Performance Characterisation of High RA Asphalt Mixes – A Laboratory and Field Study - Csaba Toth; Laszlo Petho; Szabolcs Rosta (The Baltic Journal of Road and Bridge Engineering)
The research project highlights the significance of incorporating reclaimed asphalt (RA) into hot mix asphalt (HMA) production for sustainable road construction. Despite limited RA utilization in Hungary in the past decades, the project demonstrates the feasibility of manufacturing HMA with significant RA content using advanced technology. The establishment of a capable asphalt plant and the development of laboratory assessments and mix design methodologies laid a solid foundation for future high RA integration in Hungarian road projects. Large-scale production trials confirmed the practicality of integrating high RA content into heavy-duty asphalt mixes with various binder types, including normal bitumen (B), polymer modified binder (PmB), and rubber modified bitumen (GmB). The large-scale validation project described in this paper was based on crucial binder blend designs carried out prior to the trials. Production control and performance-based laboratory testing proved that asphalt mixes can be designed and manufactured with high RA content while maintaining performance standards. Balancing resistance to distress modes like rutting and low-temperature cracking through careful binder blend design and mix design is achievable, even with high RA proportions. Visual assessments and production control indicated the uniformity of high RA content asphalt mixes. The details provided in this paper emphasise the potential for economic and environmental benefits through increased RA utilization in Hungarian road construction.